Hubungan Kompetensi Manajerial Kepala Sekolah dan Budaya Organisasi dengan Kinerja Guru - Linardo Pratama; Bradley Setiyadi (SAP (Susunan Artikel Pendidikan), 2023)
There are several factors that affect teacher performance, such as discipline, education and training, work atmosphere, compensation, principal managerial competence, responsibility, and organizational culture. Two factor were utilized in this research, that are the principal managerial competence and organizational culture. This research aims to explain The correlation between principals managerial competence and organizational culture with teacher performance in MAN 01 Indragiri Hilir Riau. Quantitative approach with correlation method was conducted to determine whether there is correlation between. The population were all teachers in MAN 01 Indragiri Hilir Riau 2019  there numbering 70 teachers. And the sample at once. Data analysis used Partial Least Square (PLS) through the Smart PLS program version 3.0 data measurement including Outer Model and Inner Model, Boostrapping, and Blindfolding. The results showed that: (1) there was a significant positive correlation between the principal managerial competence with teacher performance with a P-Value <0,10 which was 0,039 with a coefficient value of 0,238 and (2) there is a significant positive correlation between organizational culture and teacher performance with a P-Value <0,10 which is equal to 0,000 with a coefficient value of 0,646.